Teaching What, Where, Whom, and for What Purpose? – This Volume Leaves Readers Puzzled, at Best (KULT_online, 2012)
Teaching Cultural Studies aims to provide ideas and models for course designs and learning techniques, to suggest suitable secondary and primary sources to be used in teaching, and to reflect on the methodological thinking that should feed into cultural studies teaching. Unfortunately, the volume remains unfocused: it is unclear what 'cultural studies' is understood to be and whether the volume is directed toward instructors or students; issues specific to teaching cultural studies in "German tertiary education," (p. 7) which the volume claims to address, are not in fact raised. Due to this lack of positioning, teaching goals remain undefined. It is similarly unfortunate that the individual essays focus on 'matter,' that is on content, much more than on 'methods,’ 'models,’ and a reflection on those methods. These shortcomings arise from the conception of the volume rather than from the individual contributions: some articles provide great teaching inspiration as well as reflections on specific challenges.